Dynamics of Depletion and Replenishment of Water Storage in Stem and Roots of Black Spruce Measured by Dendrometers - Turcotte, Audrey; Rossi, Sergio; Deslauriers, Annie; Krause, Cornelia; Morin, Hubert (Frontiers in Plant Science, 2011)
In the short term, trees rely on the internal storage of water because it affects their ability to sustain photosynthesis and growth. However, water is not rapidly available for transpiration from all the compartments of the plant and the living tissues of the stem act as a buffer to preclude low water potentials during peaks of transpiration. In this paper, electronic dendrometers were used from mid-June to mid-September 2008 to compare the radius variations in stem and roots of black spruce [Picea mariana (Mill.) B.S.P.] in two sites of the boreal forest of Quebec, Canada, with different soil characteristics and water retention. The duration of the daily cycles was similar between sites and measurement heights but greater amplitudes of contraction and expansion were observed on the stem and in the site with the shallowest soil organic layer. The expansion phase had higher amplitudes and lasted longer than contraction. On average, the contraction phase occurred between 07:00 and 16:30 (legal time), while expansion lasted 14.5 h. The roots in the site with the deepest organic layer showed a wider variation in the onset of contraction, which could be as late as 13:00. The probability of observing the contraction phase depended on precipitation. With a precipitation <0.5 mm h-1, the bivariate posterior probabilities estimated >60% probability of observing contraction between 05:00 and 21:00, decreasing to 20% with precipitation >1.1 mm h-1. These findings demonstrated that the depth of the organic layer plays an important role in maintaining the internal water reserve of trees. The dynamics of water depletion and replenishment can modify the water potential of xylem and cell turgor during the enlargement phase, thus affecting radial growth. Changes in temperature and precipitation regime could influence the dynamics of internal water storage in trees growing on shallower and drier soils.